Induced radioactivity in AB-BNCT: an analysis of the different facilities worldwide - Capoulat, M. E.; Kreiner, A. J. (Frontiers in Nuclear Engineering, 2023)
The global effort to establish Accelerator-Based Boron Neutron Capture Therapy (AB-BNCT) facilities involves several accelerator technologies and neutron-producing reactions, with different properties in terms of the primary beam and neutron spectra they produce. This paper's primary objective is to quantitatively assess residual radioactivity in these facilities, considering both primary and secondary activation. Primary activation occurs from proton or deuteron beam interactions with accelerator subsystems, with the target material being especially critical for primary activation. On the other hand, secondary activation results from neutron-induced reactions in exposed elements, making the Beam Shaping Assembly (BSA) a critical subsystem due to its proximity to the neutron-producing target.The paper provides an in-depth analysis of activation at the target level and within the BSA, conducting a comprehensive evaluation of commonly used materials to identify significant neutroninduced reactions leading to induced radioactivity.To assess activation, representative BSAs are simulated using the MCNP 6.1 code. The study calculates the accumulated activity concentration for each material and compares it to clearance levels from the IAEA Safety Guide RS-G1.7. Additionally, cooling times required to release these materials from regulatory control are calculated throughout the facilities' lifespan.Overall, this research aims at contributing to the optimization and long-term sustainability of the AB-BNCT facilities from a radioprotection point of view.